Minimization of Real Power Loss and Augmentation of Static Voltage Stability Margin by Enhanced Algorithm - Lenin Kanagasabai (Journal of Telematics and Informatics, 2018)
This paper presents a new Enhanced African Wild Dog Algorithm (EAWDA) for solving the multi-objective reactive power dispatch problem.Inspired by Basic African wild dog algorithm (AWDA), this paper progresses by adding rounding up behaviours of wild dog, The proposed (EAWDA) algorithm has been tested on standard IEEE 30 bus test system and simulation results shows clearly about the noble performance of the projected algorithm.